2019
DOI: 10.1002/dvg.23281
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR/Cas9 engineering to generate a mouse with a conditional knockout allele for the promyelocytic leukemia zinc finger transcription factor

Abstract: Summary The promyelocytic leukemia zinc finger (PLZF) transcription factor mediates a wide‐range of biological processes. Accordingly, perturbation of PLZF function results in a myriad of physiologic defects, the most conspicuous of which is abnormal skeletal patterning. Although whole body knockout of Plzf in the mouse (Plzf KO) has significantly expanded our understanding of Plzf function in vivo, a conditional knockout mouse model that enables tissue or cell‐type specific ablation of Plzf has not been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 31 publications
(53 reference statements)
0
27
1
Order By: Relevance
“…To generate a conditional Otp knockout allele, we inserted LoxP sites to flank exon 2 of the mouse Otp gene using the CRISPR‐Cas9 system (Hai, Szwarc, Lanza, Heaney, & Lydon, 2019; Zhi, Kanaji, Fu, Newman, & Newman, 2020). To this end, we first designed and validated sgRNAs targeting the intronic sequences flanking exon 2 of the mouse Otp gene.…”
Section: Resultsmentioning
confidence: 99%
“…To generate a conditional Otp knockout allele, we inserted LoxP sites to flank exon 2 of the mouse Otp gene using the CRISPR‐Cas9 system (Hai, Szwarc, Lanza, Heaney, & Lydon, 2019; Zhi, Kanaji, Fu, Newman, & Newman, 2020). To this end, we first designed and validated sgRNAs targeting the intronic sequences flanking exon 2 of the mouse Otp gene.…”
Section: Resultsmentioning
confidence: 99%
“…An experiment on mice with a conditional knockout allele for the PLZF factor, created using Crispr/Cas9 engineering and gene editing, showed that PLZF mediated a wide range of biological processes and confusion in its function led to countless physiological defects and removing PLZF takes into account its performance. Thus, due to the remarkable speed and accuracy, Crispr genome engineering has been used to produce the conditional elimination allele PLZF in mice, and it was stated that the PLZF/f mice are a valuable tool for better describing the function of PLZF in speci c tissues and cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, a large, multi-center study reported inconsistent results using the two gRNAs/two ssODNs approach [ 8 ], where only 11 out of 56 loci were successful, possibly due to some technical differences from Yang et al [ 9 ]. In the meantime, at much smaller scales, multiple floxed models have been reported by microinjection of two gRNAs and two ssODNs along with Cas9 as IVT [ 10 – 12 ] or protein [ 13 , 14 ] as well as electroporation of gRNA/Cas9 RNPs plus ssODNs of embryos [ 15 ], or oviducts [ 16 ], with the latter requiring a substantially higher concentration of RNPs and ssODNs. Yet, it is not clear how reliable the two gRNAs/two ssODNs approach is.…”
Section: Introductionmentioning
confidence: 99%